Rancang Bangun Sistem Informasi Komunitas Burung Murai Batu Pati Berbasis Web - Ahmad Irvan; Endang Supriyati; Tri Listyorini (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
The number of stone magpie lovers and breeders with many who capture the beauty of their birds through social media uploads. Because magpies have beautiful patterns and chirps, many people have become lovers and breeders. Currently magpie bird lovers follow the competition getting information from whatsapp messages. This becomes an obstacle, when there are communities that do not have whatsapp or miss information. Magpie bird lovers and breeders still need a system to interact, discuss, and find information about magpie birds in one place. This research has the benefit of providing a place for magpie bird lovers and breeders to interact easily so that a website-based Pati magpie bird community information system is developed. With a website-based system, magpie bird lovers are more updated in getting information. The data collection methods used in this research are interviews, observations and documentation. Interviews were conducted by interviewing stone magpie bird lovers followed by observing system requirements. This system was created using the codeigniter framework and using the research development method, namely waterfall.